CFD simulation using fluent to determine the heat transfer coefficient of a packed bed system - Lim, Sing Wee (2012)
In this research, a packed bed is used in the heat exchanger will be considered. Particle to fluid heat transfer coefficient is a primal important when analyzing the performance of a heat exchanger. Basically, a bed packed consists of 44- spherical aluminium particles with proper arrangements is located inside a pipe wall will be considered in this research. A hot fluid is flowing through the packed bed in a solid pipe wall and from here, there will be a pressure drop though this system regarding to the fluid mechanic mechanism. Besides, temperature difference between fluid and solid will cause the convection process and from here heat transfer coefficient can be determined. After the results are taken from the numerical experiment, a comparison between the experimental results with past researcher's results can be done and together with the comparison of calculation using relevant formula.